Comparison of the Chemical Compositions and Antibacterial Activities of Two Iranian Mustard Essential Oils and Use of these Oils in Turkey Meats as Preservatives - Adeli Milani, Morteza; Ghobadi Dana, Maryam; Ghanbarzadeh, Babak; Alizadeh, Ainaz; Ghasemi Afshar, Peymaneh (Applied Food Biotechnology, 2019)
Background and objective: Iranian mustard is cultivated in southern areas of Iran and used traditionally as natural preservative. Aims of the current study were identification and comparison of the chemical compositions and antibacterial activities of two Iranian mustard essential oils and assessment of these oils use for increasing the shelf life of turkey meats. Material and methods: Chemical compositions of two Iranian mustard essential oils were identified using gas chromatography-mass spectrometry and antibacterial activities of these oils were assessed against Salmonella typhimurium, Escherichia coli, Citrobacter freundii, Pseudomonas aeruginosa, Staphylococcus aureus, Listeria monocytogenes, Bacillus cereus and Enterococcus faecalis using disc diffusion and broth macrodilution assays. Inhibitory effects of the essential oils were assessed on growth of mesophilic psychrotrophic bacteria, yeasts and molds and sensory evaluation was carried out for the turkey meats. Results and conclusion: Results of GC-MS showed presence of bioactive constituents, especially allyl isothiocyanate (75.87-80.07%). All the bacterial growth, especially for Escherichia coli, was inhibited with inhibition zones of greater than 20 mm and minimum inhibitory and bactericidal concentrations of 0.156 mg ml-1. Treatment of turkey meat samples with the mustard essential oils significantly decreased the count of mesophilic psychrotrophic bacteria, yeasts and molds during 20 days of storage at 4°C ±1, compared to controls (P≤0.05). Over the time, the sensory score of the treated samples increased, compared to controls. Based on these findings, the Iranian mustard essential oils can be used as natural preservatives in foods. Conflict of interest: The authors declare no conflict of interest.